Masalah yang Dialami Wanita Pedagang Kaki Lima (PKL) dan Implikasinya bagi Bimbingan Konseling - Asmidir Ilyas (Ilmu Pendidikan: Jurnal Kajian Teori dan Praktik Kependidikan, 2002)
This studi was aimed at describing the problems faced by women working as street-vendors. The sample consisted of 98 female street-vendors (PKL) in five cities of West Sumatera using cluster proportional random sampling. The data were collected through interview and analyzed statistically using percentage technique. The findings indicated that the problems faced by the women in household were lack of time to educate their children and conflicts with their husbands. The problems seemed to have some implications to the practices of guidance and counseling done through the out-of-school programs.